Effects of water and nutrient addition on the coppice growth response of cut Terminalia sericea. - Moyo, H.; Scholes, M.C.; Twine, W. (AOSIS OpenJournals Publishing AOSIS (Pty) Ltd, 2016)
The ability of a woody plant to coppice and remain vigorous largely depends on the severity of disturbances, resource availability and the mobilisation of stored reserves. There is limited information about the role played by resource limitation on the recovery of cut trees. This study investigated the effects of water and nutrient supplementation on coppice growth responses of resprouting cut trees in a semi-arid savannah in South Africa. Cut trees were exposed to different levels of water and nutrient (nitrogen and phosphorus) supplementation over a period of 2 years in a factorial experimental design. We hypothesised that adding water and nutrients would result in an increased coppice growth response and replenishment of stored structural reserves. Adding water and nutrients significantly increased shoot diameter, shoot length and resprouting ratio for the initial 12 months after cutting but not stored structural reserves. Such a response pattern suggests that the initial growth of resprouting shoots may be strongly resource-limited, while resources are concentrated on supporting fewer resprouting shoots compared to a higher number. Conservation implications: If practicing rotational tree harvesting, trees resprouting in resource-poor locations need a longer resting period to recover stored reserves and to also recover lost height after cutting.
Keywords: Terminalia sericea; water; nutrients; coppice; trees; ecosystems; Biological diversity; conservation